Optimalisasi Beban Pajak Wajib Pajak Orang Pribadi melalui Pemilihan Status Perpajakan - Made Andy Pradana Sukarta; I Dewa Agung Nanditiya Putra; Ni Kadek Cahya Dwi Utami; I Wayan Adnyana; I Gede Nata Mintara (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the optimization of individual income tax (PPh) burden through the selection of tax filing status, namely joint filing (KK) and separate filing (PH/MT), in the Indonesian taxation system. The research employs a descriptive quantitative approach using a comparative simulation method based on variations in income distribution between spouses. The data used are secondary data derived from prevailing tax regulations, including progressive income tax rates and non-taxable income thresholds (PTKP). The results indicate that the efficiency of tax status selection is conditional. In cases where the wife earns income from a single employer, joint filing (KK) is more advantageous, as the wife’s income is treated as effectively final and does not significantly increase the progressive tax burden. Conversely, when income is derived from multiple sources or includes non-final income components, the difference between joint and separate filing tends to be insignificant in terms of tax payable. These findings highlight that the choice of tax filing status should be determined analytically by considering income structure, marginal tax rates, and applicable tax regulations. This study contributes both practically, by providing guidance for taxpayers in optimizing their tax burden, and theoretically, by enriching the literature on individual tax planning strategies.